2022
DOI: 10.36834/cmej.75591
|View full text |Cite
|
Sign up to set email alerts
|

Emerging concepts in the CanMEDS physician competency framework

Abstract: Background: The CanMEDS physician competency framework will be updated in 2025. The revision occurs during a time of disruption and transformation to society, healthcare, and medical education caused by the COVID-19 pandemic and growing acknowledgement of the impacts of colonialism, systemic discrimination, climate change, and emerging technologies on healthcare and training. To inform this revision, we sought to identify emerging concepts in the literature related to physician competencies. Methods: Emerging … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 41 publications
2
34
0
Order By: Relevance
“…Our study identified eleven emerging concepts in the literature that could guide or inform the development of paramedic competencies. Each of these concepts is broad, and similar to the findings of Thoma et al [17], they mirror broader influences in paramedicine, healthcare, and society as a whole over the last decade. We will now briefly discuss a number of observations in our findings.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Our study identified eleven emerging concepts in the literature that could guide or inform the development of paramedic competencies. Each of these concepts is broad, and similar to the findings of Thoma et al [17], they mirror broader influences in paramedicine, healthcare, and society as a whole over the last decade. We will now briefly discuss a number of observations in our findings.…”
Section: Discussionsupporting
confidence: 59%
“…Informed by the findings of Thoma et al [17] and Van Melle [18], we modified their original terms to reflect the differences in language between physicians and paramedics, and to reflect elements guiding the methodology of the NOSP development process such as the principles guiding paramedicine in Canada [5] and a systems thinking conceptual framework [9]. One author (AB) analysed the extracted data and deductively categorised results into emerging concepts.…”
Section: Discussionmentioning
confidence: 99%
“…We conducted continuous content analysis to identify emerging concepts that were related to or could inform paramedic competencies. Informed by the frameworks of Thoma et al [ 17 ] and Van Melle [ 18 ], we modified their original emerging concepts to reflect: a) the differences in language between physicians and paramedics; and b) the methodology of the NOSP development [ 5 , 9 ]. For example, we changed 'physician humanism' [ 17 ] to 'healthy professionals' [ 5 ].…”
Section: Reviewmentioning
confidence: 99%
“…2 Despite multiple calls for specific VC training, [3][4][5][6] these concepts were identified as being underrepresented in the 2015 CanMEDS physician competency framework 7 by a recent literature review. 8 CanMEDS 2025 must be updated to reflect these novel competencies, ensuring that today's physicians are able to meet their patients' and societies' evolving needs. For this primer, we propose changes to the CanMEDS competencies that focus on the skills necessary to connect virtually with patients and peers to deliver effective remote consultation and patient care.…”
Section: Introductionmentioning
confidence: 99%